2002
DOI: 10.1002/art.10576
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of type II collagen synthesis and degradation predicts progression of joint damage in patients with knee osteoarthritis

Abstract: Objective. The hallmark of osteoarthritis (OA) is the loss of articular cartilage. This loss arises from an imbalance between cartilage synthesis and cartilage degradation over a variable period of time. The aims of this study were to investigate the rates of these processes in patients with knee OA using two new molecular markers and to investigate whether the combined use of these markers could predict the progression of joint damage evaluated by both radiography and arthroscopy of the joints during a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
204
6
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 264 publications
(228 citation statements)
references
References 37 publications
16
204
6
2
Order By: Relevance
“…This observation was consistent with previous reports (19)(20)(21)26,28). Because urinary CTX-II levels reflect the degradation of cartilage type II collagen in all body joints, including the * The odds ratio (OR) was adjusted for sex, age, and body mass index.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This observation was consistent with previous reports (19)(20)(21)26,28). Because urinary CTX-II levels reflect the degradation of cartilage type II collagen in all body joints, including the * The odds ratio (OR) was adjusted for sex, age, and body mass index.…”
Section: Discussionsupporting
confidence: 89%
“…Because the levels of bone markers in serum or urine mainly reflect the overall rate of skeletal turnover, which can be affected by different conditions independent of OA, they are likely to lack sensitivity to detect focal abnormalities of subchondral bone metabolism, a factor that may explain the inconsistent and somewhat disappointing data generated between markers of bone turnover and joint damage in OA (3,4). In contrast, several studies have shown a consistent association between increased baseline levels of urinary CTX-II and more rapid progression of radiographic knee or hip OA over the subsequent 1-6 years (19)(20)(21). Additionally, we previously showed that decreased urinary CTX-II levels over 3 months in patients with early rheumatoid arthritis who were treated with an active combination of prednisolone, methotrexate, and sulfasalazine were associated with slower radiographic progression over the subsequent 5 years (30), suggesting that early changes in this marker may be related to long-term progression, although this hypothesis needs to be confirmed in OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association between mean BMI and JSL was not found in a recent review (26). Our results are in contrast with studies showing a positive association between increased urinary CTX-II levels and progression of knee (33) or hip (34) OA, but are consistent with a study by Mazzuca et al, who found no relationship between urinary CTX-II and JSL (35). Type II collagen constitutes the most abundant protein of intervertebral discs.…”
Section: Knee Joint Space Study In Womensupporting
confidence: 79%
“…In this issue of Arthritis & Rheumatism, Garnero et al confirm and extend these observations (23). They also show that the amino propeptide of an apparently minor splice variant of type II procollagen, type IIA collagen, is detectable in serum even in healthy adults.…”
Section: Can Serum Biomarker Assays Measure the Progression Of Cartilmentioning
confidence: 71%